Regulation of Yeast Cytokinesis by Calcium - Chen, Qian (Journal of fungi (Basel), 2025)
The role of calcium, an essential secondary messenger, in cell division remains an outstanding question in cell biology despite several significant findings over the past few decades. Among them is the landmark discovery of intracellular calcium waves during cytokinesis, the last stage of cell division, in fish cells. Nevertheless, subsequent studies have been largely unable to determine the underlying molecular mechanism of these cytokinetic transients. At the center of this stalemate stands two challenging questions, how these calcium transients rise and what they do during cytokinesis. Yeast, despite its proven prowess as a model organism to study cell cycle, has not drawn much interest in addressing these questions. However, the recent discovery of cytokinetic calcium spikes in the fission yeast Schizosaccharomyces pombe has provided novel insights into how calcium regulates cytokinesis. In this review, I will primarily focus on our current understanding of the molecular mechanism of cytokinetic calcium transients in yeast cells. First, I will briefly recount the discovery of cytokinetic calcium transients in animal cells. This will be followed by an introduction to the intracellular calcium homeostasis. Next, I will discuss yeast cytokinetic calcium spikes, the ion channel Pkd2 that promotes these spikes, and the potential molecular targets of these spikes. I will also compare the calcium regulation of cytokinesis between yeast and animal cells. I will conclude by presenting a few critical questions in our continued quest to understand how calcium regulates cytokinesis.